Comparison of depression and anxiety among pacemaker and implantable cardioverter‐defibrillator recipients: A cross‐sectional study. Issue 2 (12th January 2021) - Rafsanjani, Mojgan Haj Ahmadi Pour; Masoudi, Sima; Radmanesh, Majid; Bostani, Zahra
Abstract: Introduction: Anxiety and depression among implantable cardioverter‐defibrillator (ICD) recipients can lead to physical or psychological consequences and reduce the quality of life of these patients. Few studies have compared the frequency and severity of depressive and anxiety disorders in the pacemaker (PM) and ICD recipients. The aim of the present study was to compare depression and anxiety among PM and ICD recipients. Methods: This cross‐sectional study was performed on 296 patients referred to a specialized cardiology teaching hospital from October 1, 2019 to July 1, 2020. Patients were selected using convenience sampling method. Results: Regarding anxiety, the results showed that the overall prevalence of anxiety in PM, ICD, and control groups was 23.5%, 28%, and 8%, respectively. Results showed no significant difference between PM and ICD recipients regarding the anxiety prevalence ( p = .46). With regard to depression, the results showed that the overall prevalence of depression in the PM, ICD, and control groups was 7.1%, 23%, and 4.1%, respectively. The results showed a significant difference between PM and ICD recipients in terms of depression prevalence ( p = .03). The results also showed that the prevalence of depression was significantly higher among PM and ICD recipients than the control group ( p = .01). Conclusion: Considering the results of the present study and the high prevalence of anxiety and depression, it seems necessary to focus more on educating patients about the effectiveness of PM and ICD devices in reducing anxiety and depression.